Causes of stillbirths and neonatal deaths in Dhanusha district, Nepal: A verbal autopsy study - Manandhar, SR; Ojha, A; Manandhar, DS; Shrestha, B; Shrestha, D; Saville, N; Costello, AM; Osrin, D (Kathmandu University Medical Journal, 2010)
Background: Perinatal (stillbirths and first week neonatal deaths) and neonatal (deaths in the first 4 weeks) mortality rates remain high in developing countries like Nepal. As most births and deaths occur in the community, an option to ascertain causes of death is to conduct verbal autopsy. Objective: The objective of this study was to classify and review the causes of stillbirths and neonatal deaths in Dhanusha district, Nepal. Materials and Methods: Births and neonatal deaths were identified prospectively in 60 village development committees of Dhanusha district. Families were interviewed at six weeks after delivery, using a structured questionnaire. Cause of death was assigned independently by two pediatricians according to a predefined algorithm; disagreement was resolved in discussion with a consultant neonatologist. Results: There were 25,982 deliveries in the 2 years from September 2006 to August 2008. Verbal autopsies were available for 601/813 stillbirths and 671/954 neonatal deaths. The perinatal mortality rate was 60 per 1000 births and the neonatal mortality rate 38 per 1000 live births. 84% of stillbirths were fresh and obstetric complications were the leading cause (67%). The three leading causes of neonatal death were birth asphyxia (37%), severe infection (30%) and prematurity or low birth weight (15%). Most infants were delivered at home (65%), 28% by relatives. Half of women received an injection (presumably an oxytocic) during home delivery to augment labour. Description of symptoms commensurate with birth asphyxia was commoner in the group of infants who died (41%) than in the surviving group (14%). Conclusion: The current high rates of stillbirth and neonatal death in Dhanusha suggest that the quality of care provided during pregnancy and delivery remains sub-optimal. The high rates of stillbirth and asphyxial mortality imply that, while efforts to improve hygiene need to continue, intrapartum care is a priority. A second area for consideration is the need to reduce the uncontrolled use of oxytocic for augmentation of labour. Key words: Stillbirth; neonatal death; verbal autopsy; Nepal. DOI: 10.3126/kumj.v8i1.3224 Kathmandu University Medical Journal (2010), Vol. 8, No. 1, Issue 29, 62-72